2011
DOI: 10.4028/www.scientific.net/amm.55-57.1436
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Argon Pressure on the Structural and Physical Properties of LaB<sub>6</sub> Films

Abstract: Lanthanum hexaboride (LaB6) films were deposited on Si (111) substrates by magnetron sputtering method. The characterization of the films was investigated by means of atom force microscopy (AFM), X-ray diffraction (XRD), four-point probe electrical resistance measurement, scratch tester and nano-indentation tester. Influence of argon pressure on physical properties, such as crystallization degree, conductivity and mechanical properties was studied. All the films were smooth and dense. The film crystallites sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For LaB x film, the working pressure plays a very important role in the deposition process. Zhao et al [ 32 ] pointed out that LaB 6 thin films, which were deposited at 1.0 Pa, have a higher degree of crystalline structure and superior physical properties in comparison with the other films. Hu et al [ 33 ] also reported that argon pressure strongly influenced the condensing particles’ kinetic energy clearly by affecting the scattering processes of sputtered energetic particles and LaB 6 film deposited at 1.0 Pa showed a higher crystallinity degree.…”
Section: Resultsmentioning
confidence: 99%
“…For LaB x film, the working pressure plays a very important role in the deposition process. Zhao et al [ 32 ] pointed out that LaB 6 thin films, which were deposited at 1.0 Pa, have a higher degree of crystalline structure and superior physical properties in comparison with the other films. Hu et al [ 33 ] also reported that argon pressure strongly influenced the condensing particles’ kinetic energy clearly by affecting the scattering processes of sputtered energetic particles and LaB 6 film deposited at 1.0 Pa showed a higher crystallinity degree.…”
Section: Resultsmentioning
confidence: 99%